Antisense oligonucleotide eluforsen improves CFTR function in F508del cystic fibrosis - Sermet-Gaudelus, Isabelle; Clancy, John P.; Nichols, David P.; Nick, Jerry A.; De Boeck, Kris; Solomon, George M.; Mall, Marcus A.; Bolognese, James; Bouisset, Florilene; den Hollander, Wilhelmina; Paquette-Lamontagne, Nicolas; Tomkinson, Nigel; et al. (Journal of cystic fibrosis, 2019)
Background - Cystic fibrosis (CF) is caused by mutations in the CF transmembrane conductance regulator (CFTR) gene. In this study we assessed the effect of antisense oligonucleotide eluforsen on CFTR biological activity measured by Nasal Potential Difference (NPD) in patients with the most common mutation, F508del-CFTR. - Methods - This multi-centre, exploratory, open-label study recruited adults with CF homozygous or compound heterozygous for the F508del-CFTR mutation. Subjects received intranasal eluforsen three times weekly for 4weeks. The primary endpoint was the within-subject change from baseline in total chloride transport (Cl-free+iso), as assessed by NPD. Secondary endpoints included within-subject change from baseline in sodium transport. - Results - In the homozygous cohort (n=7; per-protocol population), mean change (90% confidence interval) in Cl-free+iso was −3.0mV (−6.6; 0.6) at day 15, −4.1mV (−7.8; −0.4, p=.04) at day 26 (end of treatment) and−3.7mV (−8.0; 0.6) at day 47. This was supported by improved sodium transport as assessed by an increase in average basal potential difference at day 26 of +9.4mV (1.1; 17.7, p=.04). The compound heterozygous cohort (n=7) did not show improved chloride or sodium transport NPD values. Eluforsen was well tolerated with a favourable safety profile. - Conclusions - In F508del-CFTR homozygous subjects, repeated intranasal administration of eluforsen improved CFTR activity as measured by NPD, an encouraging indicator of biological activity.